PENGARUH LIKUIDITAS DAN PROFITABILITAS TERHADAP PENGUNGKAPAN ISLAMIC SOCIAL REPORTING PADA BANK UMUM SYARIAH INDONESIA - Murni Murni; Imam Malik; Nurul Ula (Negotium: Jurnal Ilmu Administrasi Bisnis, 2023)
This research aims to determine the influence of liquidity and profitability on the disclosure of Islamic Social Responsibility in Sharia Commercial Banks in Indonesia in 2019-2021. Using a quantity approach with secondary data, namely the annual financial reports of Sharia Commercial Banks in Indonesia for the 2019-2021 period. The data analysis technique uses multiple linear regression so thatthe results obtained are that liquidity and profitability have no effect on Islamic Social Responsibility in Sharia Banking in Indonesia for the 2019-2021 period, simultan or partially